CHARACTERIZATION OF THE EXTERNAL PROTEINS OF HAMSTER FIBROBLASTS - Hynes, Richard O. (The Rockefeller University Press, 1974)
The results of metabolic labeling studies and enzymatic treatments followed by analysis on polyacrylamide gels show that the external proteins of hamster fibroblast cell lines, which have been identified by lactoperoxidase-catalyzed iodination, do not contain sulphated mucopolysaccharides or hyaluronic acid and are probably unrelated to collagen. Several of the iodinated species comigrate with carbohydrate-containing molecules. In particular, the major iodine-labeled polypeptide of normal fibroblasts appears to be a glycoprotein. This glycoprotein is absent or much reduced in virus-transformed cells, as detected both by iodination and by metabolic labeling. We conclude that the major iodinated polypeptide is not detected on transformed cells because it is absent rather than because it is masked. Approximate molecular weights of the external proteins are also reported.